ANALYSIS OF HYBRID OPERATIONS AND MANAGEMENT DECISIONS TO COUNTER SUCH PHENOMENA IS FOREIGN EXPERIENCE - Hranovskyi , Mykola (Pressing Problems of Public Administration, 2021)
The beginning of the ХХІ century is characterized by new challenges in the field of international security. It is believed that the end of the Cold War did not eliminate domestic or regional sources of conflict and did not ensure the stable peaceful coexistence of countries in the world. According to experts, the international community is facing not so much a direct armed conflict, but one of the types of military operations, which can also be called hybrid. In today’s world there is a tendency to significantly in crease the number of hybrid conflicts, which are becoming more sophisticated and unpredictable. The article is devoted to theoretical and practical aspects of such phenomena as hybrid war, hybrid conflict or aggression, which affect the security of the international environment, as well as the actions of public authorities to counter such threats, in particular in the EU. During the analysis of this question, an attempt was made to answer the following questions: “What is the essence of hybrid actions? How is their evolution? What is the nature of today’s hybrid aggression?”. The arguments presented in the material confirm the need for further research into hybrid actions that have violated the integrity of the state borders of many countries, including Ukraine, and continue to pose a real threat to security in Europe and the world. The current practice of hybrid operations on the part of the aggressor demonstrates a radical change in the tactics and means used by the world-class player state against the enemy, who is weak and unable to defend the integrity of its own territory. The power of the aggressor state, combined with the elements of a hybrid war, proves the weakness of international security institutions, and the international agreements that have been proven of have been called in to question. Although in the most experts believe that the failure to stop the conflict in eastern Ukraine at the present stage will lead to a growing threat of destabilization of the entire region of Central and Eastern Europe.